Beyond Solutionism: Differently Motivating Media Literacy - McDougall, Julian (2022)
This article discusses three research projects conducted in partnerships in diverse societies. We assess the implications of each project for media literacy’s motivations and intentionality through a theory of change. For the first project, BBC Media Action, we developed the theory of change which frames this article and a media literacy training programme for in-country practitioners to strengthen media ecosystems and support resilience to information disorder. Our second project was Dual Netizenship, a youth-led, intercultural partnership between Tunisia and the UK at the intersection of media literacy, civic agency, and decolonisation. Thirdly, Digital Arts—Refugee Engagement (DA-RE) brought together refugee youth in Bangladesh and Turkey to combine media literacy and digital artivism with civic capability development. The status of media literacy as a conduit for positive change (rather than a solution in itself) was different in each partnership—from the production of counter-script youth-led media to capacity-building for refugee participants in host communities to the situating of “mainstream media” itself as the agent of positive intervention in the ecosystem. Our theory of change situates media literacy as a form of context-bound capability development as opposed to a set of neutral, universal competences. The research that we share here was conducted with “third space” media literacy design principles. In addressing both the positive change initiated by these projects and the tensions and challenges in play in the motivating imperatives of partnerships, the article speaks to the complexity of media literacy in diverse societies.